PROGRAM PHARMA CARE 2025: EDUKASI NARKOBA, HIV/AIDS, SKRINING KESEHATAN, DAN UJI FORMALIN UMKM DESA BANJARSARI - Dinda Paramudita; Nindi Adinta; Dewi Meilia Agustin; Sintia Audina; Yayang Mutiara Marcellina; Yulis Adriana (Berajah Journal, 2026)
The Pharma Care 2025 program is a community service initiative aimed at improving public knowledge, awareness, and health status in Banjarsari Village, Ciawi District, Bogor Regency. This program was motivated by the increasing cases of drug abuse (NAPZA), the risk of HIV/AIDS transmission, and the high prevalence of degenerative diseases in the community. The methods used included observation, health education, screening, and community empowerment through a participatory approach. The activities implemented consisted of health screening, drug abuse and HIV/AIDS education for adolescents, education on degenerative diseases and dementia, vitamin distribution, formalin testing in food products, and a herbal soap-making workshop. The screening results indicated that a significant proportion of the community had high cholesterol and uric acid levels, suggesting a risk of degenerative diseases. Health education activities were proven effective in improving participants' knowledge, as indicated by an increase in average pretest–posttest scores among students from 83.67 to 92, and among community members from 65.86 to 83.79. In addition, formalin testing on food samples showed negative results, indicating relatively safe food conditions. The herbal soap workshop successfully enhanced community skills in utilizing natural resources for economically valuable products. Overall, this program had a positive impact on increasing health awareness, promoting healthy lifestyle changes, and strengthening community economic empowerment. This initiative is expected to serve as a sustainable promotive and preventive intervention model to improve public health quality.